PEMBERDAYAAN MASYARAKAT KELURAHAN PASAR BARU KOTA TANJUNG BALAI DALAM BUDIDAYA LOBSTER AIR TAWAR - Mahary, Azizah; Tambunan, Syafrida Br; Nurhadi, Nurhadi; Pahmi, Pahmi; Ridwan, Lokot; Rahmania, Abdul (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
Community empowerment is an important effort to improve the welfare and economic independence of the community. This research aims to evaluate the effectiveness of material socialization in empowering the people of Pasar Baru Village, Tanjung Balai City, through cultivating freshwater lobsters. The method used is the distribution of printed and digital materials which include technical guidance on cultivating freshwater lobsters, as well as direct outreach to the public. The research results showed that the socialization of the material was successful in increasing basic knowledge and public interest in cultivating freshwater lobsters. As many as 80% of participants reported increased understanding and interest in being involved in this cultivation business. Apart from that, outreach materials also increase public awareness of the importance of environmentally friendly cultivation practices. Although material dissemination is effective in disseminating information, limitations in the form of information delivery (without practical training) pose a challenge in implementing the knowledge gained. To achieve more optimal results, a more comprehensive approach is needed that includes practical training, technical guidance and market access support. This research concludes that material dissemination is an important first step in empowering the community through cultivating freshwater lobsters. However, to achieve sustainable success, more holistic and integrated follow-up efforts are needed.